Energy security and sustainable energy policy in Bangladesh: From the lens of 4As framework. (February 2022) - Amin, Sakib Bin; Chang, Youngho; Khan, Farhan; Taghizadeh-Hesary, Farhad
Abstract: Energy security is considered the constituent element of sustainable development for an emerging country like Bangladesh. We aim to investigate Bangladesh's energy security level by employing the 4As framework from 2014 to 2019. We reveal that Bangladesh's energy security showed a declining trend from 2014 and reached a minimum in 2016. However, from 2017 onwards, it started to show an improving trend compared to 2014. The improvements mainly come from the Availability and Applicability dimensions; however, the Acceptability and Affordability dimensions still show that country is yet to achieve proper energy security. We argue that despite the recent success in the energy sector and the subsequent improvement in the energy security level, further concrete policy initiatives are required for sustainable energy security in the long-run. We recommend symmetrical improvement policies in all of the 4As dimensions for future sustainable energy security in Bangladesh. Highlights: Bangladesh's energy security showed a declining trend from 2014. From 2017 onwards, it started to show an improving trend. The improvements mainly come from the Availability and Applicability. The Acceptability and Affordability dimensions are still low. Symmetrical improvement policies in all of the 4As dimensions are needed.